Biliary Rhabdomyosarcoma in an Infant Male With Neurofibromatosis Type 1. Issue 1 (January 2019) - Alhashem, Fatema; Yilmaz, Ebru; Ozdemir, Mehmet A.; Deniz, Kemal; Yikilmaz, Ali; Patiroglu, Turkan; Karakukcu, Musa; Unal, Ekrem
Abstract : Different types of malignancies can be seen in patients with neurofibromatosis type 1 (NF-1). Herein we present a rare combination of NF-1 and biliary rhabdomyosarcoma in a male infant. An 11-month-old boy, who was recently diagnosed with NF-1, presented to the outpatient clinic with a 3-month history of prolonged jaundice, and failure to thrive. Clinical examination showed >20 café au let spots distributed mainly over the abdominal trunk. Hepatomegaly (4 cm below the costal margin) was additionally observed. His father was diagnosed with NF-1. Radiologic imaging studies showed a 6×5×5 cm in diameter cystic mass with multiple septations in the segment 4A of the liver. Surgical excision of the left hepatic lobe followed by hepatojejunostomy was further performed. Histopathology examination showed embryonal type rhabdomyosarcoma originating from the biliary duct. Chemotherapy regimen consisting of cyclophosphamide, actinomycin D, and vincristine, and radiotherapy were then initiated. This treatment led to a significant improvement in the patient's clinical status, and radiologic finding portrayed attainment of complete resolution. He is still in complete remission without any sequelae for 8 years.